The Plight of Refugees in ASEAN Member Countries - Macaraig, Christine Elizabeth; Mursyid, Fariz Pradipta (Technium Social Sciences Journal, 2021)
This paper identifies and analyzes the efforts of ASEAN member states in addressing the contemporary threats and hardships experienced by refugees. The situation is further exacerbated by the pandemic brought about by the COVID-19 coronavirus. As an international organization, ASEAN is expected to have a collective and cooperative strategy to address this. However, ASEAN member states do not exhibit large-scale collaborative efforts to resolve the plight of the refugees. Rather, mutual agreements seem to be limited to the host/transit country and the native country of the refugees. Liberal institutionalist theory that emphasizes the function of international institutions to aid multinationals cooperation in certain areas is used to explain ASEAN’s role to deal with the plight of refugees in South East Asia. It is recommended for ASEAN members to re-examine the potential of international relations in securing a safer and sustainable future for refugees.